Navigating the Seas of Diplomacy: ASEAN's Role in Shaping the Indo-Pacific Outlook - Lesza Leonardo Lombok,; Jirehsya Carmel Marsanda Baliung,; Sam Julius Richard Saroinsong,; Harly Rumagit,; Arthur Novy Tuwaidan, (Technium Social Sciences Journal, 2024)
The Indo-Pacific region has become essential for global trade and security, with its significance increasing due to the emergence of China and India. ASEAN, as a regional organization consisting of ten Southeast Asian countries, plays a vital role in shaping the region's outlook by fostering regional cooperation, economic integration, and security. This paper explores the challenges and opportunities ASEAN faces in shaping the Indo-Pacific outlook and seeks strategies for ASEAN to effectively navigate diplomatic waters. Through a normative legal method, it is found that ASEAN encounters challenges such as conflicts involving major powers, potential disputes over member sovereignty, and the necessity to respond assertively to external pressures. ASEAN's inclusive and consensus-based approach is appreciated by many regional actors. The ASEAN Outlook on the Indo-Pacific (AOIP) emphasizes inclusivity and cooperation, aligning with the interests of both major powers and smaller states. To navigate diplomatic challenges and shape the Indo-Pacific outlook, ASEAN can actively participate in regional and international forums, promote dialogue and cooperation, and utilize its existing mechanisms and networks.